PENINGKATAN PERILAKU KERJA ISLAMI DENGAN BUDAYA ORGANISASI ISLAMI SEBAGAI VARIABEL MODERASI - Diah Ayu Kusumawati (Conference In Business, Accounting, And Management (CBAM), 2015)
This study aimes to analyze the influence of islamic leadership style, Islamic work ethic and islamic organizations culture to conduct Islamic work behavior in Sultan Agung Islamic University of Semarang. The purpose of this study was to determine the role of organizational culture islamic to moderate the relationship between leadership style islamic and islamic work ethic in Islamic work behavior of the lecturer and staff at the Sultan Agung Islamic Univercity of Semarang. Data were obtained from 1 60 respondents to the questionnaire. Data analysis using SPSS 16 shows that the Islamic leadership style has a significant and positive influence on the islamic work behavior, the islamic work ethic have a significant and positive effect of the reactor islamic work behavior, islamic leadership style has a positive and significant impact on the islamic work ethic, and islamic organizational culture may moderate the relationship between islamic leadership style and islamic work ethic against the islamic work behavi or of the lecturer and staff at the Sultan Agung Islamic University of Semarang. Â Keywords: islamic leadership style, islamic work ethic, islamic organizational culture, islamic work behavior